Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/0883073818799155
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of and Risk Factors for Hydrocephalus in Childhood Bacterial Meningitis

Abstract: Objective: To explore the clinical characteristics of and analyze the risk factors for hydrocephalus in children with bacterial meningitis. Methods: Retrospective study of a sample of children with bacterial meningitis seen on the pediatric service of Shengjing Hospital of China Medical University between January 1, 2010, and December 31, 2016. Results: Overall, 9.36% (25/267) of patients presented with hydrocephalus. Among patients with hydrocephalus, the age at onset of bacterial meningitis was usually <6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
(40 reference statements)
1
18
1
Order By: Relevance
“…Regarding the most common neurological complication in our study, hydrocephalus, the incidences of 28.1 and 19.5 % in the nosocomial and community-acquired groups, respectively, are notably higher than the 9.4 % reported in a 2019 single institution Chinese study of 267 paediatric BM patients [17]. A 2018 study of 85 paediatric BM patients age <90 days in Taiwan reported the incidence of hydrocephalus to be 18.8 %, though it is unclear how that diagnosis differs from ventriculomegaly, which was reported in 41.2 % [18].…”
Section: Discussioncontrasting
confidence: 75%
“…Regarding the most common neurological complication in our study, hydrocephalus, the incidences of 28.1 and 19.5 % in the nosocomial and community-acquired groups, respectively, are notably higher than the 9.4 % reported in a 2019 single institution Chinese study of 267 paediatric BM patients [17]. A 2018 study of 85 paediatric BM patients age <90 days in Taiwan reported the incidence of hydrocephalus to be 18.8 %, though it is unclear how that diagnosis differs from ventriculomegaly, which was reported in 41.2 % [18].…”
Section: Discussioncontrasting
confidence: 75%
“…Alterations in cerebrospinal fluid parameters have been identified as predictors of severe neurologic complications, including hydrocephalus. 2,14 -18 Cerebrospinal fluid glucose <2 mmol/L was identified as a risk factor for hydrocephalus in our study. However, Huo et al 2 did not reach the same conclusion in the study of children under 14 years old, which may be related to the higher cerebrospinal fluid glucose level in newborns than that in older children.…”
Section: Discussionsupporting
confidence: 46%
“…3,28 Another study also found that Escherichia coli was the main cause of meningitis with hydrocephalus, accounting for 40%. 2 Hydrocephalus often occurs in the early stage of Escherichia coli meningitis, and ependyma enhancement is usually shown on MRI, which reflects that the occurrence of hydrocephalus may be related to severe inflammation of meningitis. 4,28 And the increase of cerebrospinal fluid leukocytes (>100×10 6 /L) in our study also indicated that inflammation plays an important role in the development of hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-infectious hydrocephalus (PIH) refers to hydrocephalic progression triggered by infection or severe inflammation in the brain tissue [16]. Most commonly, postnatal contraction of meningitis can introduce external pathogens to the developing nervous system and induce PIH [53][54][55]. Inflammation could also be conferred prior to birth or during delivery, such as via TORCH infections, which initiate immune cell activation along the maternal-placental-fetal axis, and can result in PIH [56][57][58].…”
Section: Other Forms Of Hydrocephalusmentioning
confidence: 99%